‘AKU TERBAKAR AMARAH SENDIRIAN’: PENA PRAMUDYA DI BAWAH REZIM SOEHARTO - Dina Dyah Kusumayanti (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2018)
This article aims at examining Pramudya Ananta Toer’s Buru Tetralogy. Many literary scholars have studied this tetralogy from the points of view of nationalism, posctolonialism, and feminism. However, this article presupposes that this tetralogy is conscpicuous especially regarding the political nuance of the ruling regime and some political issues encountered by the protagonist, Minke. Sosiology of literature is the approach underpinning the scrutiny of four novels incorporated in the tetralogy. Swingewood’s sociology of literature helps this current research to find any relation between the political and historical background of the novels and detils on the political issues found in them. Results show that some political agendas in the novel have proven equal to some political agendas under the Soeharto regim. Oligopoly and oligarchy in the novels which are practiced by the regim is an instance to this. This paper elucidated the regim’s political decisions and the political events confronted by Minke. Constraint of this research is on its textual examination of Pram’s tetralogy Buru. In order to investigate these literary texts and the historical political moments under Soeharto’s regime, further research on the historical and political events of the regime need to be elucidated and have to refer to the historical and political documents and medias.